TaSPL14-7A is a conserved regulator controlling plant architecture and yield traits in common wheat (Triticum aestivum L.) - Cao, Lina; Li, Tian; Geng, Shuaifeng; Zhang, Yinhui; Pan, Yuxue; Zhang, Xueyong; Wang, Fang; Hao, Chenyang (Frontiers in Plant Science, 2023)
Plant architecture is a crucial influencing factor of wheat yield and adaptation. In this study, we cloned and characterized TaSPL14, a homologous gene of the rice ideal plant architecture gene OsSPL14 in wheat. TaSPL14 homoeologs (TaSPL14-7A, TaSPL14-7B and TaSPL14-7D) exhibited similar expression patterns, and they were all preferentially expressed in stems at the elongation stage and in young spikes. Moreover, the expression level of TaSPL14-7A was higher than that of TaSPL14-7B and TaSPL14-7D. Overexpression of TaSPL14-7A in wheat resulted in significant changes in plant architecture and yield traits, including decreased tiller number and increased kernel size and weight. Three TaSPL14-7A haplotypes were identiﬁed in Chinese wheat core collection, and haplotype-based association analysis showed that TaSPL14-7A-Hap1/2 were signiﬁcantly correlated with fewer tillers, larger kernels and higher kernel weights in modern cultivars. The haplotype effect resulted from a difference in TaSPL14-7A expression levels among genotypes, with TaSPL14-7A-Hap1/2 leading to higher expression levels than TaSPL14-7A-Hap3. As favorable haplotypes, TaSPL14-7A-Hap1/2 underwent positive selection during global wheat breeding over the last century. Together, the findings of our study provide insight into the function and genetic effects of TaSPL14 and provide a useful molecular marker for wheat breeding.